The Effect Of Lamong River Flow Diversion To Bed Surface Degradation - Ikhsan, Cahyono (Jurnal Teknik Sipil dan Perencanaan, 2020)
Abstract Kali Lamong River with a trapezoidal channel shape has a bottom width of about 30 m, a top width of 40 m and a depth of 3.5 m. In one of the river segments, the basis is in the form of a fixed bed and it is assumed that there is no sediment transport in this section. On the downstream side after the fixed bed section, the river segment is a mobile bed with river bed material that has an average grain diameter of 1.5 mm, a relative mass density of 2.6, and porosity of 0.3. Flowrate with Q50 is 1000.00 m3/sec with a maximum flow speed of 15 m/sec. Riverbed degradation will occur initially at the upstream point in the fixed and mobile beds. Depth of riverbed degradation calculated by the Parabolic model of 80.00 cm / year based on the solution of the equation.